Influence of person-organization fit on job satisfaction among pre-service preschool teachers of China: Mediation of teaching self-efficacy and perceived teacher competence - Lu Xing; Xueqi Wu (PLoS ONE, 2026)
In China, a growing number of preschool education majors demonstrate reluctance to enter the profession upon graduation, posing a challenge to the sustainable development of the early childhood education workforce. Internships represent a critical period for pre-service teachers to develop their professional identity and capabilities. This study investigates the sustainability of pre-service teacher internships by examining the relationship between person-organization (P-O) fit and teachers’ job satisfaction, specifically focusing on the mediating roles of teaching self-efficacy and teaching competence. A quantitative survey was conducted with 493 pre-service preschool teachers (males 10.5%, females 89.5%) from Changsha Normal University between April and May 2024. Using Structural Equation Modeling (SEM), an integrated model of “values/needs matching → self-efficacy → competency development → teachers’ job satisfaction” was tested. The results indicate that P-O fit has a significant positive association with pre-service teachers’ job satisfaction, teaching self-efficacy, and teaching competence. Furthermore, teaching self-efficacy and teaching competence mediate the relationship between P-O fit and teachers’ job satisfaction, both independently and through a chain mediation effect. These findings suggest that to enhance the sustainability of internships and future retention, higher education institutions and kindergartens should prioritize value alignment and the progressive development of interns’ efficacy and competence.